2023
DOI: 10.1038/s12276-023-00984-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of the genomic mutation signature and tumor mutation burden on relapse risk prediction in head and neck squamous cell carcinoma after concurrent chemoradiotherapy

Abstract: Personalized genetic profiling has focused on improving treatment efficacy and predicting risk stratification by identifying mutated genes and selecting targeted agents according to genetic testing. Therefore, we evaluated the role of genetic profiling and tumor mutation burden (TMB) using next-generation sequencing in patients with head and neck squamous cell carcinoma (HNSC). The relapse mutation signature (RMS) and chromatin remodeling mutation signature (CRMS) were explored to predict the risk of relapse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This could also imply that TMB thresholds may differ depending on the clinical stage and extent of prior therapy in different cancers. Studies have indicated predictability in anticipating responses to ICIs in neoadjuvant or early-stage scenarios across various cancer types, including but not limited to NSCLC, melanoma, breast cancer, and HNSCC [106,[150][151][152]. A study by Niknafs, N. and colleagues has shown an association between underlying molecular alterations and the emergence of a persistent TMB that is linked to a favorable response to ICIs [153].…”
Section: Additional Considerations For Futurementioning
confidence: 99%
“…This could also imply that TMB thresholds may differ depending on the clinical stage and extent of prior therapy in different cancers. Studies have indicated predictability in anticipating responses to ICIs in neoadjuvant or early-stage scenarios across various cancer types, including but not limited to NSCLC, melanoma, breast cancer, and HNSCC [106,[150][151][152]. A study by Niknafs, N. and colleagues has shown an association between underlying molecular alterations and the emergence of a persistent TMB that is linked to a favorable response to ICIs [153].…”
Section: Additional Considerations For Futurementioning
confidence: 99%
“…However, there are still many patients who do not benefit from pembrolizumab treatment ( 7 ). Moreover, the five-year overall survival rate for individuals with HNSC continues to be < 50% ( 8 ). Therefore, there’s an urgent need to comprehensively investigate the complexities of the TME and discover new targets for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%